Eksistensi Hukum Dalam Pemanfaatan Teknologi Transaksi E-Commerce - Dungga, Weny Almoravid (Universitas Brawijaya, Indonesia, 2009)
In this time computer and the support apparatus have entered in every work and life aspect. The computers now have ability which more than simply ordinary mathematic calculation. We can say that computer have entered and watered down most of all activity of human being. The study is to understand laws and regulation related with the arrangement of computer transaction e-commerce study the suitability between the national law and globalization development and describes penal policy formulation. Regulation of law support for existence of utility the technology of information, especially in the e-commerce therefore must be realized. Be in fact of this law regulation in the form of the management on relations involved in transaction and it is not management on its technology.